Effects of increasing copper and zinc from two different sources and space allowance on nursery and finishing pig growth performance and carcass characteristics - Carpenter, Corey Blaine (Kansas State University, 2017)
Five experiments using a total of 4,470 pigs were used to determine the effects of dietary Cu and Zn source and finishing pig space allowance. Experiment 1 evaluated increasing dietary Zn from Zn hydroxychloride or ZnSO₄ for finishing pigs. Increasing dietary Zn up to 100 mg/kg Zn maximized ADG and HCW with the greatest response observed during the last 37 d period when ractopamine was included in the diet. Pigs fed diets with Zn hydroxychloride had greater HCW compared to those fed ZnSO₄. Experiment 2 evaluated increasing dietary Cu from either CuSO₄ or a 50:50 blend of CuSO₄:Cu-AA for finishing pigs. Pigs fed Cu from CuSO₄ alone consumed more feed and tended to have poorer feed efficiency than those fed a 50:50 blend of Cu from CuSO4:Cu-AA. Pigs fed a 50:50 blend of CuSO4:Cu-AA had improved HCW G:F but ADG was unchanged on a live and HCW basis. Experiments 3 and 4 evaluated increasing dietary Cu from tri-basic copper chloride or a Cu-chelate for nursery pigs. In Exp. 3, increasing Cu from Cu-chelate to 150 mg/kg Cu increased ADG and ending BW. Increasing Cu to 150 mg/kg Cu increased ADFI and improved G:F. Pigs fed Cu from Cu-chelate had greater ADG, ADFI and ending BW than those fed Cu from tri-basic copper chloride. In Exp. 4, increasing Cu to 225 mg/kg Cu increased ADG and ending BW. Because ADFI was unchanged, G:F tended to be improved as Cu level increased. There were no differences detected between Cu sources for growth performance. Experiment 5 was conducted to determine the effects of increasing space allowance by pig removal or gate adjustment during the finishing period. Pigs provided 0.91 m² had increased ADG compared with those allowed 0.63 m² with pigs from pens provided increased space intermediate. Pigs provided 0.91 m² had increased ADFI compared with pigs allowed 0.63 m² and those where a pig was removed; however, pigs from pens where the gate was adjusted were intermediate. As pigs grew to the minimum predicted space requirement and were subsequently allowed more space, performance was greater than those initially provided 0.61 m² but less than those allowed 0.91 m².
Keywords: Carcass characteristics; Copper; Nursery pig; Space; Zinc